The influence of knowledge and skills on the attitudes of primary school mathematics teachers in Sabah in online classroom assessment: Pengaruh pengetahuan dan kemahiran terhadap sikap guru matematik sekolah rendah di Sabah dalam pentaksiran bilik darjah secara dalam talian - Sincaroo, Bawani; Linus , Noemi; A.D Matsud , Afinah; Syariff M Fuad, Dayang Rafidah; Justin, Donatus; Majid, Nuraziella (Jurnal Pendidikan Bitara UPSI, 2023)
This study was conducted to review the implementation of online PBD for the Knowledge and Skill aspect towards the Attitude of Mathematics teachers in rural upper schools in Sabah. The study also aims to determine the influence of teachers' knowledge and skills on their attitudes while conducting online PBD. The study used a survey method involving 244 respondents. Data analysis was performed using SPSS version 26 and Structural Equation Modelling, SEM Amos Version 24. The final model fit index was obtained with RMSEA=0.067, CFI=0.929, TLI=0.921, and Chisq/df=1.980. The study found that the Knowledge and Skill of Teachers contributed 46% to the teacher's attitude while conducting online PBD. Knowledge contributed 18 units to the improvement of teachers' attitudes, and Skill contributed 57 units to the improvement of teachers' attitudes. Overall, it was found that the Attitude of Teachers in conducting online PBD was more influenced by their Skills. The findings of this study are very important for the Malaysian Ministry of Education (KPM) to plan a long-term training plan to improve Mathematics teachers' skills in conducting online PBD.